Challenges for ontological engineering in the humanities: a case study of philosophy. (2016) - Garbacz, Pawel
The paper develops an idea of an engineering ontology whose purpose is to represent philosophy as a research discipline in the humanities. I discuss three recent attempts in this respect with the aim to identify their modelling potential. The upshot of this analysis leads to a new conceptual framework for ontological engineering for philosophy. I show how this framework can be implemented in the form of an OWL ontology.